DEVELOPMENT OF INVENTORY LOGISTICS - Gaffarov Mahammatzokir Toshtemirovich; Ilhamaliyev son of Ulugbek Qakhramon (Journal of new century innovations, 2022)
Annotation: This article provides information on the reasons for the accumulation of reserves and reserves, technological and transition reserves, classification of material reserves, basic reserve control systems and production management.